Quantitative approaches to linguistic diversity : commemorating the centenary of the birth of Morris Swadesh - Wichmann, Søren, 1964-; Grant, Anthony, 1962-; Swadesh, Morris, 1909-1967 (Benjamins current topics., 2012)
Quantitative methods in linguistics, which the protean American structuralist linguist Morris Swadesh introduced in the 1950s, have become increasingly popular and have opened the world of languages to interdisciplinary approaches. The papers collected here are the work not only of descriptive and historical linguists, but also statisticians, physicists and computer scientists. They demonstrate the application of quantitative methods to the elucidation of linguistic prehistory on an unprecedented world-wide scale, providing cutting-edge insights into issues of the linguistic correlates of subs.